Standard Operating Procedure of Covid-19 Game : Using Game as a Platform to Spread Awareness on The Standard Operating Procedure of Covid-19 - Ahmad Nor Ziddan Muhammad Khatib; Suhaili Din (Journal of Computing Technologies and Creative Content, 2022)
Two years that have passed since Covid-19 was first found in Malaysia. Malaysia has faced a catastrophic loss of life and strange challenges to public health, food systems, and the labour market in the past. To avoid the problem from worsening, a standard operating procedure (SOP) for managing people's everyday lives is required. Creating a game in the style of Monopoly but shifting the emphasis to the SOP is practical. Rather, understanding and remembering the SOP throughout the epidemic will be far more enjoyable and approachable for the younger generation. This game's objective is to teach and continually remind young people about the SOP. The project's goals are to raise awareness about SOP, build a game that would teach and remind the younger generation about SOP, and assess the game's efficacy as a means of spreading SOP knowledge. Adobe Animate will be utilized to create the game. The Game Development Life Cycle Model (GDLC) served as a guide for the development of this project, which included Initiation, PreProduction, Production, Testing, Beta, and Release. A test involving 30 participants aged 6 to 18 years old was conducted to evaluate the gaming application. The results and conclusions demonstrated that raising awareness through gaming applications is highly successful, and that learning SOP through games is far more engaging and amusing than through other platforms. Therefore, recommending the use of games in education is necessary in this field.